2002
DOI: 10.1210/er.2001-0022
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Receptor Antagonists: Discovery, Development, and Use in Patients with Acromegaly

Abstract: An understanding of the events that occur during GH receptor (GHR) signaling has facilitated the development of a GHR antagonist (pegvisomant) for use in humans. This molecule has been designed to compete with native GH for the GHR and to prevent its proper or functional dimerization-a process that is critical for GH signal transduction and IGF-I synthesis and secretion. Clinical trials in patients with acromegaly show GHR blockade to be an exciting new mode of therapy for this condition, and pegvisomant may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
198
0
10

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(211 citation statements)
references
References 208 publications
1
198
0
10
Order By: Relevance
“…The GH receptor antagonist pegvisomant (peg) is a treatment option for acromegaly, if disease activity could be adequately controlled by other treatments such as surgery, somatostatin analogues or dopamine agonists (1,2). It is a pegylated human GH analogue, which blocks the GH receptor (3).…”
Section: Introductionmentioning
confidence: 99%
“…The GH receptor antagonist pegvisomant (peg) is a treatment option for acromegaly, if disease activity could be adequately controlled by other treatments such as surgery, somatostatin analogues or dopamine agonists (1,2). It is a pegylated human GH analogue, which blocks the GH receptor (3).…”
Section: Introductionmentioning
confidence: 99%
“…Initially introduced in the bovine hormone (G119R-bGH) (15), the Gly substitution in the human hormone was also shown to generate an antagonist (G120K/RhGH), and the crystal structure of the hGH⅐hGHR 2 complex revealed that the Arg/Lys could actually impede the formation of a functional receptor dimer (14). Subsequently, these studies have resulted in the approval of a GHR antagonist, Somavert (Pegvisomant for injection), as a drug for the treatment of acromegaly (16).…”
mentioning
confidence: 99%
“…PRL , it drags along the "lower part" of the hormone (regions [15][16][17][18][19][20][21][22][23][24][25][26][27][28] PRL and 125-136 PRL ). Region 15-28 PRL reaches its final position only when the second PRLR-ECD interacts at binding site 2.…”
mentioning
confidence: 99%
“…This mechanismbased inhibitor of GH signaling works by binding to the receptor and blocking the conformational change that results in GH receptor activation. That the Gly-120 3 Arg substitution creates a GH antagonist was discovered in John Kopchick's laboratory, but the low affinity of this mutant required affinity maturation by phage display to make an effective drug, which was undertaken in Jim Wells' laboratory at Genentech (19). The eight resulting substitutions also restricted the specificity of this antagonist to hGH receptors, allowing Kaulsay et al (20) to show that blockade of GH and not prolactin receptor was able to inhibit the proliferative and cell motility activity of autocrine hGH in MCF-7 mammary carcinoma cells.…”
mentioning
confidence: 99%